Cigarette smoking and risk of suicide in bipolar disorder: a systematic review - García-Jiménez, Jesús; Gómez-Sierra, Francisco José; Martínez-Hortelano, Alicia; Moreno-Merino, Paula; Girela-Serrano, Braulio; Molero, Patricio; Gutiérrez-Rojas, Luis (Frontiers in Psychiatry, 2023)
Objective: Bipolar disorder (BD) is a highly prevalent, chronic and recurrent mental illness. The smoking rates in patients with BD are much higher than those of the general population, and BD is associated with an increased risk of suicide. An association between smoking and suicidal behaviour has been found in the general population, this systematic review examines whether there is evidence of an association between smoking and suicide behaviour in patients with BD. Method: A database search was carried out in Medline, Embase, The Cochrane Library, Scopus, and Web of Science, updated until December 31st, 2021, according to the 2020 PRISMA guidelines. We identified prospective and retrospective studies that included patients diagnosed with BD types I, II, and not otherwise specified, and in which smoking and suicidal behaviour were correlated. Articles that focused exclusively on other mental disorders were excluded. The Ottawa-Newcastle scale was used to assess the methodological quality of the included articles. Results: 15 articles (n=7,395) met all the inclusion criteria. In nine of these articles, the authors found an association between smoking and suicidal behaviour in BD, while in the remaining six articles, this association was not found. A great deal of variability was observed between articles, particularly in the measurement of suicidal behaviour and tobacco consumption. The risk of bias, as assessed by the NOS, was high for most of the included articles, except for two, whose risk was low. Conclusions: It was not possible to establish a clear relationship between tobacco use and the risk of suicide in BD patients due to the heterogeneity of the articles included in this systematic review, which had different sample sizes and methodological issues. However, both conditions are highly prevalent and have a negative impact on the prognosis of BD. Therefore, a systematic approach is needed, based on accurate measurement of a patient's smoking habits and risk of suicidal behavior, in order to establish an appropriate therapeutic plan. Additional information: This research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors and was registered on PROSPERO with the CRD42022301570 on January 21th 2022.